The growth performance and survival of Clarias gariepinus fry raised in homestead concrete tanks (2012)
Fertilizer application in earthen ponds has been used as a low-cost method of sustainable aquaculture production. This study was carried out to investigate the growth response of African catfish fry, Clarias gariepinus in three different culture media in homestead concrete tanks. The water in the control (T1) was not treated while T2 and T3 were treated with poultry droppings and soy bean milk filtrate, respectively. Nine hundred catfish fry weighing averagely 0.67-0.69 g were randomly allocated to the 3 treatments in equal number. In each tank (2x3x1.5 m) were suspended, 3 net cages each of dimension, 1x1x1 m containing 100 fry. The fish in tank 1 (control treatment) were fed fish meal from the start at 5% of their body weight and four times daily. The other treatments were not fed at all for the first 7 days. Feeding with fishmeal commenced for treatments T2 and T3 on the next 8-14 day. The weights of the feed were adjusted after weekly weighing of the culture media for phytoplankton composition. The best weight increase was recorded in T1 (2.33 g). The highest survival rate was in T3 (98%). Treatment T3 (11.56±1.14x103) generated higher concentrations of most of identified zooplanktons than treatments T1 (5.39±0.73x103) and T2 (12.78±0.98x103). These zooplanktons were absent in treatments T1 and T2. The result indicates that fertilizing the culture medium using soybean milk filtrate or poultry droppings improved the growth and of C. gariepinus.